Bunch bagging effect on fruit setting and quality of fruit in different litchi germplasm - Hossen, M A; Ahmad, M; Islam, M A; Rokonuzzaman, M (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was carried out at the BAU Germplasm Centre (GPC), Bangladesh Agricultural University, Mymensingh during February to May, 2021 to study the effect of bagging on fruit setting and fruit quality of different litchi germplasm. The experiment was laid out in a Randomized Complete Block Design with three replications of four litchi germplasms viz. Mongolbari, China-3, Bombai, Mozzafforpuri. Here replication number is represented by number of plants observed per variety. The data were recorded on number of fruit set per inflorescence, fruit dropping, fruit color, weight per fruit, TSS (% brix). At marble stage, bunch bagging was done with brown and white polypropylene bag and while the bunches were without bagging in control plants. Bunch bagging has significantly influnced on yield and yield contributing traits of litchi germplasms. The highest fruit setting was obtaining from the combination of Bombai litchi with brown polyethylene bag followed by Mongolbari with white polyethylene bag, while non-bagged China-3 obtained the lowest fruit setting. Mongolbari variety had highest TSS (18.65% Brix) in brown polypropylene bag treatments. Highest average fruit weight (21.15g) was found in Bombai variety on brown polypropylene bag treatment and lowest average fruit weight (12.83g) from China-3 variety on control treatment. Fruit color i.e. deep purple, moderate purple, deep red, pale yellow and no/less fruit cracking, no bird damage was found on bunch bagging treatment in fruit ripening of litchi which may add more consumer value of litchi fruit. Based on the study it can be concluded that as a good agricultural practices (GAP) brown polypropylene bunch bagging treatment was the best to reduced fruit dropping as well as increased the average fruit weight, fruit color and %TSS value of litchi fruit. Timely establishment of bunch bagging in litchi orchard is beneficial to ensure better fruit set, reduce fruit dropping, prevent insect infestation, reduce bird damage and better sugar content of litchi. Bangladesh J. Nuclear Agric, 38(2): 81-88, 2024